A new technique of autologous bone grafting for open-wedge high tibial osteotomy - Gong, Yongchao; Jin, Lin; Wang, Yanwei; Liu, Boxu; Shen, Pengfei; Zhang, Zhiang; Yuwen, Peizhi; Zhao, Kuo; Ma, Lijie; Chen, Wei; Zhang, Yingze (Frontiers in Surgery, 2024)
Purpose This study aimed to demonstrate the application of orthotopic bone flap transplantation with a fibula transplantation (OBFT-FT) in open-wedge high tibial osteotomy (OW-HTO) and to assess the effect of OBFT-FT on gap healing. Patients and methods From January to July 2020, 18 patients who underwent OW-HTO with OBFT-FT were reviewed for this study. Demographics, postoperative complications, and radiological and clinical outcomes of patients were collected. Finally, the clinical outcomes of patients were analyzed. Results A total of 14 patients were included in this study. The average age and body mass index were 59.6 ± 9.2 years and 28.1 ± 4.5 kg/m2, respectively. The average correction angle and gap width were 9.5 ± 1.8° and 10.2 ± 2.7 mm, respectively. The rates of radiological gap healing at sixth week, third month, and sixth month were 42.9%, 85.7%, and 100%, respectively. The mean Lysholm score, International Knee Documentation Committee score, and visual analog scale scores at sixth-month follow-up were significantly better than the preoperative scores (p < 0.001, p < 0.001, p = 0.001, respectively). And, no delayed union or non-union, collapse, loss of correction, or surgical site infection were found. Conclusions As a new technique for autologous bone graft, the OBFT-FT could be successfully applied in the treatment of gap healing after OW-HTO, and excellent radiological and clinical outcomes could be seen on patients’ short-term follow-up.